Preliminary results of a counselling programme for fertility preservation in female cancer patients: The experience of the GEMME DORMIENTI network. (30th September 2019) - Ciccarone, Mariavita; Hohaus, Stefan; Pulsoni, Alessandro; Cavaceppi, Paola; Franzò, Simona; Fabbri, Raffaella; Cudillo, Laura; Battistini, Roberta; Di Rocco, Alice; Annibali, Ombretta; Cox, Maria Christina; Provenzano, Ida; et al.
Abstract: Objective: To describe a population of patients referred for fertility preservation (FP), how to efficiently provide FP care, and how FP care changed over time. Methods: This longitudinal observational study enrolled 281 female cancer patients referred between 2013 and 2016 to the non‐profit organisation Gemme Dormienti ONLUS (GD) for FP care. All patients underwent the same battery of instrumental and laboratory diagnostic tests. GnRHa therapy was started at least seven days before CTh treatment. Results: From 2013 to 2016, we observed a progressive increase in the number of patients referred for FP care. Out of 251 eligible patients, 135 patients were treated with GnRHa only, and 72 patients underwent GnRHa therapy and cryopreservation. The median time from GD referral to oocyte and ovarian tissue cryopreservation was 11 and 5 days respectively. Tissue cryopreservation requests increased during our study period (from four cases in 2013 to 17 cases in 2016). During follow‐up, 17β‐estradiol and FSH levels were significantly increased ( p  < .0001), and AMH levels were significantly decreased ( p  < .0001). Conclusion: The rapid increase in the number of patients who requested FP care and in the complexity of FP procedures overtime reflects the need to improve quality of life for cancer patients.